Simulating individual, group, and crowd behaviors in building egress. (September 2015) - Chu, Mei Ling; Parigi, Paolo; Law, Kincho H; Latombe, Jean-Claude
Studies of past emergency events have revealed that occupants' behaviors, local geometry, and environmental constraints affect crowd movement and evacuation. Design of egress systems should take into consideration the social characteristics of the occupants and the unique layout of the buildings. This paper describes an agent-based egress simulation tool, SAFEgress, which is designed to incorporate human and social behaviors during evacuations. The unique feature of SAFEgress is its flexibility to model different individual, group, and crowd behavior. Simulations are conducted to examine egress performance of a museum floor plan for three scenarios: (1) expected occupancy load during peak hours; (2) group behaviors among museum visitors; and (3) measures to reduce pre-evacuation delay. By assuming different occupants' behaviors in the simulations, engineers, designers, and facility managers can study the important human and social factors on an egress situation and, thereby, improve the design of safe egress systems and procedures.